Laryngopharyngeal Diphtheria: Still a Diagnosis in Indian Adults - Kumar Agarwal, Vinish; Singh Bist, Sampan; Kumar, Lovneesh; Dhasmana, Gunjan (ENT Updates, 2021)
Diphtheria is an acute, potentially fatal, and highly communicable bacterial infection caused by Corynebacterium diphtheriae. In India and the developing world, 100% immunisation is claimed against diphtheria through diphtheria, pertussis, and tetanus (DPT) vaccination. Only a negligible number of cases are seen in the western world. In India, a few outbreaks of diphtheria has been reported among children. But it is rarely diagnosed in Indian adults. Diphtheria has high morbidity due to nerve damage and high mortality because of respiratory obstruction or myocardial complications. PubMed data base was searched for case reports in last 10 years for respiratory diphtheria in adults. Here we are presenting our case and a review on laryngopharyngeal diphtheria in adults.